The Journey of Muhammed Bey al-Alfi to London: An Eye-Opening Journey - Kandil, Doaa A. M..
Through close analysis of a wide array of archival sources like Foreign Office Records and War Office Records as well as diverse contemporary sources like chronicles, memoires, correspondences, and press, this article provides an investigation of the journey of the Mamluk chief Muhammad bey al-Alfi to London in 1803 on behalf of the Mamluk beys of Egypt. It seeks to illuminate the various aspects of this journey was shrouded in obscurity and left out of the prevailing historical narrative. The paper also highlights the underlying motives of this journey as well as its implications on the Mamluk institution. It also outlines the diplomatic, economic and social activities that Alfi bey conducted there. It argues that this journey was truly an eye-opening experience if not a life-altering one for Alfi bey. Evidently, it had a lasting impact on him and helped him to articulate a new political vision by its end. As a result, he returned back Egypt with a recipe for its progress and a full determination to initiate an entire political makeover.  doi: http://dx.doi.org/10.5913/jarce.53.2017.a006